A “reverse direction” technique of single-port left upper pulmonary resection - Zhang, Min; Sihoe, Alan D. L.; Du, Ming (Journal of Thoracic Disease, 2016)
Background: Single-port video-assisted thoracoscopic surgery (VATS) left upper lobectomy is difficult amongst all the lobes. At the beginning of single-port lobectomies, the upper lobes were believed not to be amenable for single-port approach due to the difficult angulation for staplers. Gonzalez reported the first single-port VATS left upper lobectomy in 2011. Methods: We report a new technique of single-port VATS left upper lobectomy with the concept of “reverse direction”. We divide the apical-anterior arterial trunk with upper vein in the last. The procedure sequence is described as follows: posterior artery, lingular artery, bronchus and finally upper vein & apical-anterior arterial trunk. Results: This method could overcome the angular limitations frequently encountered in single-port VATS procedures; reduce the risk of injuries to pulmonary artery; broaden the indications of single-port the upper lobe of the left lung (LUL) to include hypoplastic lung ﬁssures. Limitations of this new practice include the enlargement or severe calcifications of hilar and bronchial lymph nodes. Conclusions: A “reverse direction” technique of single-port left upper pulmonary resection is feasible and safe.